2022
DOI: 10.1101/2022.09.26.509546
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A national professional development program fills mentoring gaps for postdoctoral researchers

Abstract: The Postdoc Academy: Succeeding as a Postdoc was designed to build postdocs' skills in career transition, career planning, collaborative research, resilience, and self-reflection. This study examined self-reported changes in five skills as learners progressed through the course. Data were collected from participants who responded to both pre- and post-surveys and engaged with the course learning activities. Results from repeated measures multivariate analysis of variance revealed that all of the self-reported… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…A recent example is the Inclusive STEM Teaching Project, a similarly structured, blended delivery course with asynchronous online content through edX and project-trained local learning community facilitators [ 47 ]. In addition, the NIH-funded Postdoc Academy project developed two asynchronous online courses targeting postdoc professional development, again also offered with local learning communities called Postdoc Academy Learning Sessions (PALS) [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent example is the Inclusive STEM Teaching Project, a similarly structured, blended delivery course with asynchronous online content through edX and project-trained local learning community facilitators [ 47 ]. In addition, the NIH-funded Postdoc Academy project developed two asynchronous online courses targeting postdoc professional development, again also offered with local learning communities called Postdoc Academy Learning Sessions (PALS) [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mentoring is a learned skill, developed through training, mutual discussions, practice and feedback (Hokanson and Goldberg, 2018). Over the past decade, research mentor training has grown from an area of relative weakness (Cole et al, 2016) to an area which has demonstrated more widespread implementation, changing both practice and perspectives (Pfund et al, 2014;Gandhi et al, 2019;Hamer et al, 2019;Desai et al, 2021;Alidina et al, 2022;Sun, T., et al, 2023). Yet, mentorship in LMICs remains challenged by few training hubs and platforms, poor institutionalization, turnover and loss of expertise, and limited recognition and funding [Hansoti et al, 2019;Oppong et al, 2021; Health research mentorship in low and middle-income countries (HERMES), 2022].…”
Section: Introduction: Background and Rationale For The Educational A...mentioning
confidence: 99%